Anthropometric and anaerobic fitness profile of elite and non-elite female soccer players - Sedano, S.; Vaeyens, R.; Philippaerts, R. M.; Redondo, J. C.; Cuadrado, G. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM: The main aim of the current study was to compare the anthropometrical and fitness profile of female soccer players by level and by playing positions. The second purpose was to explore correlations between kicking speed on the one hand and anthropometric features and explosive strength on the other. METHODS: Female soccer players (N.=190) were tested divided in two groups: elite group (N.=100) and non-elite group (N.=90). Body mass, height, leg length, body composition, counter movement jump, drop jump and kicking speed with both legs were measured. RESULTS: After controlling for experience with multivariate analysis of covariance (MANCOVA), body mass, body fat and muscle mass differed significantly by level. MANCOVA also revealed that all the anthropometrical variables differed by playing position. However, MANCOVA did not show significant differences by level of play, neither for explosive strength nor for kicking speed but revealed significant differences among playing positions. There were significant positive correlations between body mass, height, leg length, muscle mass, counter movement jump height, drop jump height and experience on the one hand and kicking speed with dominant and non-dominant leg on the other for the elite and non-elite players. CONCLUSIONS: Elite players differ from their non-elite counterparts in terms of anthropometrical features, while explosive strength and kicking speed are not sensitive enough to distinguish between levels. On the other hand, the findings indicate few positional variations, and only goalkeepers, tend to have a specific anthropometric and fitness profile. Anthropometric variables, explosive strength and experience have an influence on kicking speed.